2018
DOI: 10.1016/j.tics.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Validity in Bilingualism Research and the Bilingual Advantage

Abstract: Traditional research in bilingualism has consistently found that switching languages is effortful, placing demands on neural systems of cognitive control. This finding runs counter to most bilinguals' intuitive experience. We review a body of recent work showing that, in fact, when bilinguals switch languages voluntarily, both the behavioral cost of switching and the associated recruitment of cognitive control areas are greatly reduced or completely eliminated. This suggests that switching languages is not inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 105 publications
3
46
0
Order By: Relevance
“…These findings suggest that bilinguals who report higher engagement in a dual-language context and inter-sentential switching, also report higher intra-sentential switching. This supports current evidence that bilinguals tend to produce both types of language switches naturally especially under voluntary language switching contexts (e.g., Blanco-Elorrieta and Pylkkänen, 2018 ; Yow et al, 2018 ). This also highlights the fluidity between the dual-language context and dense code-switching context.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that bilinguals who report higher engagement in a dual-language context and inter-sentential switching, also report higher intra-sentential switching. This supports current evidence that bilinguals tend to produce both types of language switches naturally especially under voluntary language switching contexts (e.g., Blanco-Elorrieta and Pylkkänen, 2018 ; Yow et al, 2018 ). This also highlights the fluidity between the dual-language context and dense code-switching context.…”
Section: Discussionsupporting
confidence: 89%
“…This is further demonstrated in more recent neural and behavioral studies that have experimentally induced the dense code-switching context (e.g., Blanco-Elorrieta and Pylkkänen, 2017 , 2018 ; de Bruin et al, 2018 ). In these studies, when bilinguals are given the freedom to switch between their languages and use them voluntarily, it is observed that language switching is minimally demanding, and perhaps even beneficial, due to the intuitive way that bilinguals naturally use both their languages.…”
Section: Introductionmentioning
confidence: 64%
“…In past decades, the concept of ecological validity has been related to various facets of psychological research, for example, the ecological validity of stimuli (Neisser, 1976;Risko et al, 2012;Jack and Schyns, 2017), the ecological validity of tasks (Smilek et al, 2006;Krakauer et al, 2017), the ecological validity of conditions (Schilbach, 2015;Blanco-Elorrieta and Pylkkänen, 2018), the ecological validity of research settings (Bronfenbrenner, 1977;Schmuckler, 2001), the ecological validity of results (Eaton and Clore, 1975;Greenwald, 1976;Silverstein and Stang, 1976), the ecological validity of theories (Neisser, 1976), the ecological validity of research designs (Rogers et al, 2005), the ecological validity of methods (Banaji and Crowder, 1989), the ecological validity of phenomena (Johnston et al, 2014), the ecological validity of data (Aspland and Gardner, 2003), and the ecological validity of paradigms (Macdonald and Tatler, 2013;Schilbach et al, 2013). However, despite the popular usage of this term, specific definitions and requirements of ecological validity are not always clear.…”
Section: The Big Umbrella Of Ecological Validitymentioning
confidence: 99%
“…With the latter method, there is even a difference as to whether pure language blocks of both languages are presented before and after the mixed language blocks (e.g., Declerck et al, 2013) or pure language blocks of one language are presented before the mixed language blocks and pure language blocks of the other language are presented after the mixed language blocks (e.g., Stasenko, et al, 2017). Gollan & Ferreira, 2009;Gross & Kaushanskaya, 2015; for a discussion, see Blanco-Elorrieta & Pylkkänen, 2018). Gollan and Ferreira (2009), for example, investigated Spanish-English bilinguals while the bilinguals could freely choose the language on each trial in the mixed language blocks (i.e., voluntary language switching).…”
Section: Language-mixing Costsmentioning
confidence: 99%